Energy savings in residential air conditioners using condensate cooling in discharge and liquid lines - Yuningsih, Nani; Sumeru, Kasni; Aldiansyah, Muhammad; Tritjahjono, Rachmad Imbang; Nugraha, Fathurahman Yudhi; Abioye, Adenkunle Moshood (Jurnal Polimesin, 2025)
This research investigates the use of condensate produced by the evaporator to cool the discharge and liquid lines in order to reduce electricity consumption in a residential split-type air conditioner (AC). The experimental setup used a 0.75 kW compressor with R32 refrigerant, where the discharge and liquid line heat exchangers were 20 cm and 15 cm long, respectively. Data were collected over 180 minutes at 5-minute intervals. Results show that using the liquid line cooler (LLC) alone reduced electricity consumption by 5.3% and increased cooling capacity by 2.3%. Using the discharge line cooler (DLC) alone reduced electricity consumption by 8.3% and increased cooling capacity by 7.3%. When both coolers were applied simultaneously (LDC mode), electricity consumption decreased by 10.9% and cooling capacity increased by 9.7%. The corresponding improvements in coefficient of performance (COP) were 9.1% (LLC), 18.6% (DLC), and 24.7% (LDC). These results indicate that using condensate to both the discharge and liquid lines is more effective in reducing electricity consumption and improving AC performance than cooling only one line.